Hydration of C4AF in the presence of other phases: A synchrotron X-ray powder diffraction study. (30th December 2015) - Cuesta, A.; Santacruz, I.; Sanfélix, S.G.; Fauth, F.; Aranda, M.A.G.; De la Torre, A.G.
Highlights: Hydration behaviour at early ages of C4 AF was studied in this work. The gypsum effect, amount of water and presence of ye'elimite were investigated. Synchrotron X-ray powder diffraction has been mainly used. A structural study for the C3 A0.845 F0.155 H6 phase was performed. The hydration of C4 AF is inhibited by the presence of pseudocubic ye'elimite. Abstract: Hydration behaviour of C4 AF in selected experimental conditions has been determined. C4 AF has been hydrated in the absence and presence of gypsum, two polymorphs of ye'elimite and different water/solid ratios. C4 AF in the presence of water hydrates to form mainly a hydrogarnet-type phase. The crystal structure of C3 A0.845 F0.155 H6 is reported from the Rietveld analysis of its synchrotron X-ray powder diffraction pattern. The hydration of C4 AF in the presence of gypsum gives AFt. However, the mixture tetracalcium aluminoferrite/gypsum/ye'elimite gives both AFt and AFm phases. C4 AF hydrated with ye'elimite in the absence of gypsum gives only AFm. Ye'elimite has inhibited tetracalcium aluminoferrite hydration.